Reduced Intensity Conditioning Followed by Related and Unrelated Allografts for Hematologic Malignancies: Expanded Analysis and Long Term Follow-Up - Dahl Warlick, Erica (Biol Blood Marrow Transplant, 2018)
Reduced intensity conditioning (RIC) extends the curative potential of allogeneic hematopoietic cell transplantation (HCT) to patients with hematologic malignancies unable to withstand myeloablative conditioning. We prospectively analyzed the outcomes of 292 consecutive patients, median age of 58 (range 19–75), with hematologic malignancies treated with a uniform RIC regimen of cyclophosphamide, fludarabine, and total body irradiation (TBI) (200 cGy) with or without anti-hymocyte globulin (ATG) and cyclosporine and mycophenolate mofetil graft versus host disease prophylaxis followed by allogeneic HCT at the University of Minnesota from 2002–2016. Probability of 5-year year overall survival (OS) was 78% for patients with indolent NHL, 53% for CML, 55% for Hodgkin Lymphoma, 40% for AML, 37% for MDS, 29% for myeloma, and only 14% for those with MPN. Corresponding outcomes for relapse were 0%, 13%, 53%, 37%, 39%, 75%, and 29% respectively. Disease risk index (DRI) predicted both survival and relapse with superior survival (64%) and lowest relapse (16%) in those with low risk score compared to 24% survival and 57% relapse in those with high/very high-risk scores. Recipient CMV positive serostatus was protective from relapse with the lowest rates in those also receiving a CMV positive donor graft (29%).The cumulative incidence of 2-year non-relapse mortality (NRM) was 26% and was lowest in those receiving a matched sibling graft at 21%, with low (21%) or intermediate (18%) HCT-CI and similar across age groups. The incidence of grade II-IV acute graft-versus-host disease (aGVHD) was 43% and grades III-IV was 27%: highest rates in those receiving a URD PBSC donor at 50%. Chronic GVHD at 1 year was 36%. Future approaches incorporating alternative GVHD prophylaxis, particularly for URD PBSC grafts and targeted post-transplant anti-neoplastic therapies for those with high DRI risk are indicated to improve these outcomes.